2008
DOI: 10.3102/0034654308320966
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Mentoring Programs: Reenvisioning Rather Than Reinventing the Wheel

Abstract: In this review, the authors trace the evolution of mentoring programs in the United States in business and academe, provide insight on the challenges associated with the study of mentoring, and identify the limited research-based studies of faculty mentoring programs that currently inform our understanding of this professional development practice in American higher education. The findings indicate that the sophistication of research has not advanced over the past decade. However, evidence does suggest that ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
205
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(223 citation statements)
references
References 42 publications
5
205
0
1
Order By: Relevance
“…To illustrate, in the European Union and in the USA, SMEs account for over 99% of all registered companies and for two-thirds to one half of total employment, respectively (Eurostat, 2011;United States International Trade Administration, 2013). In the empirical and managerial literature, mentoring has been typically described in and implicitly linked with large corporations (Kanter, 1977;Roche, 1977;Underhill, 2006;Zellers, Howard & Barcic, 2008). Furthermore, it is still unclear whether the benefits of mentoring are generalizable across cultures, considering that the bulk of mentoring research so far has taken place in Anglo-Saxon societies (Chen, Liao & Wen, 2014;Hu, Pellegrini & Scandura, 2011).…”
Section: Mentoring Receipt 11mentioning
confidence: 99%
“…To illustrate, in the European Union and in the USA, SMEs account for over 99% of all registered companies and for two-thirds to one half of total employment, respectively (Eurostat, 2011;United States International Trade Administration, 2013). In the empirical and managerial literature, mentoring has been typically described in and implicitly linked with large corporations (Kanter, 1977;Roche, 1977;Underhill, 2006;Zellers, Howard & Barcic, 2008). Furthermore, it is still unclear whether the benefits of mentoring are generalizable across cultures, considering that the bulk of mentoring research so far has taken place in Anglo-Saxon societies (Chen, Liao & Wen, 2014;Hu, Pellegrini & Scandura, 2011).…”
Section: Mentoring Receipt 11mentioning
confidence: 99%
“…[28,29] Mentorship guidelines may be used to list and explain the mentor and mentee responsibilities, goals and expectations to help minimize misunderstandings. [30][31][32] Mentorship training could focus on mentorship qualities, university expectations of mentors, communication skills necessary for effective mentoring, mentoring resources, stages of the mentoring relationship, how to find good mentors, prepare for mentorship meetings, and break up with a mentor. [33,34] To ensure consistency and stability, we recommend that mentorship programs develop clear guidelines that outline objectives, expectations, and role descriptions as well as mentorship training to support both mentors and mentees in their roles.…”
Section: Discussionmentioning
confidence: 99%
“…Relying on this kind of informal mentoring can place the mentee at a disadvantage. Marginalization of female or minority faculty members is common in many fields within academia, and places an additional barrier to developing informal mentoring relationships independent of a program (Zellers et al, 2008). Furthermore, a recent assessment of the revitalization of Kansas State University Libraries' mentoring program makes a strong case for formalized mentoring that supports the APT process.…”
Section: Mentoring Practices Among Selected Institutionsmentioning
confidence: 99%
“…Zellers et al (2008), through their evaluation of studies for mentoring programs for instructional faculty at academic institutions, identified that these benefits are consistent. They also found accelerated leadership development on the part of mentees -which does not necessarily equate to promotion -and an increased motivation on the part of mentees to mentor others later on.…”
Section: Benefits Of Mentoringmentioning
confidence: 99%